Change in capnogram waveform is associated with bronchodilator response and asthma control in children. Issue 6 (26th February 2019) - Cracco, Ophélie; Degrugilliers, Loïc; Rames, Cynthia; Bécourt, Arnaud; Bayat, Sam
Abstract: Background: Airway hyper‐reactivity, inflammation and remodeling contribute to inhomogeneity of ventilation‐perfusion ratio V A · / Q · in asthma. Short‐term variations in V . A / Q · can cause changes in expired capnographic indices. Objectives: To measure acute changes in the phase 3 slope of the volumetric capnogram after β2‐agonist inhalation (ΔSIII), for comparison with airway response based on FEV1 (ΔFEV1), and asthma control. Subjects and Methods: After ethical approval and informed consent, 72 children aged 6‐18 y, followed up for asthma underwent spirometry and capnography before and after β‐agonist inhalation through a spacer, using a side‐stream rapid infrared analyzer. Asthma control was assessed using the GINA questionnaire. Results: Children with positive reversibility tests (defined as ΔFEV1>12%) had a significantly higher ΔSIII (m ± SE: 87.4 ± 41.4) versus those with negative tests (31.3 ± 14.0%, P  = 0.001). Uncontrolled asthma was associated with a significantly larger ΔSIII (103.4 ± 64.0%, n  = 7) compared to partly controlled (52.0 ± 26.1, n  = 24; P  = 0.009) and controlled asthma (30.8 ± 16.3, n  = 41; P  = 0.003). Neither Bohr dead space nor ΔFEV1 were different between asthma control groups. Conclusions: ΔSIII was significantly larger in children with positive response to β2‐agonist, and in uncontrolled asthmatics. To our knowledge these are the first data on exhaled CO2 phase III volumetric slope change and asthma control. The observed ΔSIII could be due to an increased ventilation of inhomogeneous peripheral lung units, and merits further evaluation as a potential phenotypic biomarker in asthma.